PENGARUH PEMBERIAN TEH DAUN KELOR (MORINGA OLEIFERA LAMK.) TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU NIFAS DI WILAYAH KERJA PUSKESMAS WUNGU KABUPATEN MADIUN - Retno Wati, Dwi (LPPM STIKES HUSADA JOMBANG, 2022)
The low coverage of exclusive breastfeeding in Indonesia lead to children less entitled to got exclusive nutritious food for their growth. This is due to the lack of breast milk production. Non-pharmacological treatmen such as Moringa tea is expected to be able to increase breast milk production. The aims of study was to determine the effect of Moringa tea consumption to increasing breast milk production in Wungu Regional Publick Health Madiun Regency. This research method was using a quasi experimental study using one group prepost test design on 60 respondents. Intervention was carried out for 3 weeks to assess breast milk production between Pre and Post intervention. Data were analysis using Paired t-Test. The results showed that the average of breast milk (pre-test) was 152.00, increasing to 158.50 (post-test). There was a difference in the amount of breast milk with p value of 0.002 and a value of 0.934. The conclusion of this study was a significant effect of Moringa tea consumption to increasing breast milk production.